MOOCifying Courses: Delivery of a MOOC to Enhance University Course Activities - Nathaniel Ostashewski (Commonwealth of Learning, 2017)
Since 2012 MOOCs have been heralded as a new way of learning outside of formal university programs of study and there has been much speculation regarding their impact. While MOOCs have provided millions of global learners with access to courses, they failed to deliver the types of learning experiences and completion requirements that were hoped for. One potential iteration of MOOCs might be to blend them with existing courses offered in universities supporting links and connections between study and the outside world. This MOOCification of full-fee courses may provide another next step in the delivery of real and authentic learning. Using an empirical case study design, this project explored the MOOCification of an undergraduate preservice education course at an Australian university. The study presents evidence that blending MOOCs with classroom-based or online learning does provide higher education learners with personalized active learning opportunities. Further research on scaffolded support enabling learners to capitalize on additional aspects of networked learning in MOOCs is needed.